Fast Maturation of Splenic Dendritic Cells Upon TBI Is Associated With FLT3/FLT3L Signaling - Zhang, Jin; Li, Zhenghui; Chandrasekar, Akila; Li, Shun; Ludolph, Albert; Boeckers, Tobias Maria; Huber-Lang, Markus; Roselli, Francesco; olde Heuvel, Florian (Frontiers in Immunology, 2022)
Systemic inflammatory consequences remain a significant burden after traumatic brain injury (TBI), with almost all organs affected. The spleen is connected with the brain by autonomic innervation and by soluble mediators, and the cross-talk between brain and spleen may be important to establish the systemic inflammatory response to TBI. Ethanol intoxication, the most common comorbidity of TBI, is posited to influence the peripheral inflammatory response either directly or through the brain-spleen cross-talk. Here we show that TBI causes a substantial change in transcription of genes associated with dendritic cells activation in the spleen, in particular a FLT3/FLT3L induction 3h after TBI, which was enhanced by EI. The FLT3L induction was associated with the phosphorylation of FLT3 receptor in CD11c+ dendritic cells, which enhanced the protein synthesis of a subset of mRNAs, as shown by the increase in pS6, peIF2A levels in dendritic cells. This corresponded to the upregulation of proteins associated with maturation process and immunostimulatory properties such MHC-II, LAMP1 and CD68, and of pro-inflammatory cytokines such as TNFα. Notably, EI enhanced the maturation of dendritic cells. However, whereas TBI decreases expression of the adrenergic 2b receptors on dendritic cells, EI increased it, thus augmenting the chances of cross-talk regulation of immune function by the autonomic system. In conclusion, this data indicates that TBI induces a fast maturation of the immunomodulatory functions of dendritic cells which is associated by FLT3/FLT3L signaling and which is enhanced by EI prior to TBI.